Implementasi Penilaian Hasil Belajar Siswa Berbasis Aplikasi Raport Digital (ARD) Di MTs Negeri Kota Kupang - Muh. Amiruddin Salem; Yusuf Ali Samad (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2021)
Assessment of learning outcomes is an integral component in the implementation of education. The necessity to conduct an assessment of learning outcomes is emphasized in the Regulation of the Minister of Education and Culture Number 66 of 2013 concerning Educational Assessment Standards that these standards aim to ensure: (1) Planning of students is in accordance with the competencies achieved based on assessment principles, (2) Implementation of professional assessment of participants , open, educative, effective, efficient, and in accordance with the socio-cultural context, and (3) Reporting the results of participant assessments in an objective, accountable, and informative manner. manners. The approach used is qualitative. The type of research is case study. Data collection techniques using the method of observation, interviews, and documentation. The results obtained from this study are; 1) The Digital Report Card or ARD application is used to make it easier for teachers to process learning outcomes that have been achieved by students in the learning process. 2). In the process of inputting the assessment of student learning outcomes, 90% of teachers at MTs Negeri Kupang have been able to use the Digital Report Card (ARD) Application and 10% are still in the process of assisting ARD operators. The input of grades is done online and is connected directly to the server at the school.